Teaching Materials and Learning Media for Android-Based Receptive Language Skills with Smart Apps Creator Application Technology for Indonesian Language and Literature Education Students - Nurhayatin, Titin; Triandy, Rendy; Rustandi, Adi (Universitas Pendidikan Ganesha, 2023)
The low ability of students in receptive language is because, in the online learning process, students tend to use gadgets more to play than to study. This research aims to develop teaching materials and learning media for Android-based receptive language skills using smart apps creator application technology for Indonesian Language and Literature education students. This research belongs to the type of development research which was developed using the 4D model. The subjects involved in this research were learning media experts and Indonesian language and literature study program students. Data collection in the study was carried out using trial methods, tests, observations, questionnaires, and validation, with research instruments in the form of media validation sheets and tests of receptive language skills. The data obtained in the study were then analyzed using qualitative analysis techniques and processed through the stages of data reduction, data presentation, and verification. The data analysis showed that the media validity test results were 83, which was feasible. The average student attitude observation results were 3.74, which was in the very valid category, and the product implementation results showed 98.7% of students agreed with the display presentation, ease of understanding of the material, and the attractiveness of the design used. Based on these results, teaching materials and learning media for Android-based receptive language skills with the Smart Apps Creator application technology are in the valid category and feasible to develop in the learning process.